NUMERICAL SIMULATIONS OF A FLAT PHANTOM IN THE NEAR-FIELD OF SYMMETRIC DIPOLE ANTENNA - Styła, Monika; Styła, Sebastian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The paper presents a numerical electromagnetic simulations of SAR limited to human tissues based on FDTD algorithm using Sim4Life platform. Flat-bottomed dielectric vessel (flat phantom) and half-wave symmetric dipole antenna were modeled. Simulations were done for the frequencies 0.9 GHz and 0.6 GHz. The analysis were performed according to the IEEE/IEC62704-1 standard and include distributions of electric and magnetic fields around the phantom and antenna. Finally, SAR distributions in the phantom and near the antenna.